The Relationship between Self-Efficacy, Resilience, Social Support, and Subjective Well-being among Female Conditional Cash Transfer Beneficiaries in Panggungharjo Village, Indonesia - Septiyanti, Liana; Rahayu, Ety (International Journal of Business, Economics, and Social Development, 2025)
Understanding the psychosocial factors shaping the subjective well-being of female Program Keluarga Harapan (PKH), a conditional cash transfer program in Indonesia, beneficiaries is fundamental to evaluating intervention success beyond economic metrics. The numerous persistent challenges faced by disadvantaged women in Indonesia have been shown to influence their assessments of well-being. This paper aims to investigate the relationship between self-efficacy, resilience, social support, and subjective well-being. This study utilizes a quantitative approach, employing a survey method and a purposive sampling technique for 198 female beneficiaries of the PKH conditional cash transfer in Panggungharjo Village, Yogyakarta Province, Indonesia. Data analysis was conducted using the Somers’d correlation test using SPSS version 29. The results indicate that self-efficacy (dyx = 0.131; p>0.05) is not significantly correlated with subjective well-being. In contrast, the finding reveals that resilience (dyx = 0.257; p<0.001) and social support (dyx = 0.219; p<0.05) are positively and significantly correlated with subjective well-being. These findings confirm that resilience and social support play a crucial role in enhancing subjective well-being. These findings underscore the importance of optimizing interventions that can strengthen resilience and social support, as well as exploring additional psychological variables to understand the psychosocial dynamics of subjective well-being. This research contributes to the literature on the psychosocial condition of female conditional cash transfer beneficiaries in Indonesia, while also serving as a basis for policy formulation aimed at reducing poverty levels in Indonesia.